Trends in Paragonimiasis Global Research: Bibliometric Analysis of a Neglected Food-Borne Parasite - Altun, Serap Kilic; Aydemir, Mehmet Emin; Alkan, Sevil; Irehan, Buenyamin (Iranian Scientific Society Medical Entomology, 2023)
Background: Paragonimus is a genus of parasitic flatworms known as lung flukes that cause the parasitic disease paragonimiasis in humans and other mammals. We aimed to use bibliometric analysis to identify the global characteristics and tem-poral trends of published literature about paragonimiasis. Methods: Using the Web of Science database, we identified all original articles on paragonimiasis 1997 to 2022. After collecting the bibliographic and citation data, keywords, citation networks, and co-citations pertaining to paragonimiasis was car-ried out using the VOSviewer program. Results: The study identified 563 paragonimiasis articles published in 250 journals. Publications in paragonimiasis research have been cited 6190 times and 2803 times without self-citations. The years with the most publications were 2013, 2016, and 2021. The minimal threshold for analysis was met by 19 of the 52 countries inves-tigated. The study included 19 items, yielding 170 links between countries. The to -tal strength of these links was discovered to be 104772. The journal with the most publications in this category was Parasitology Research (n=31). The most frequent-ly used terms in paragonimiasis study were paragonimiasis, Paragonimus wester-manii, and lung-fluke. Conclusion: The study concluded by providing an overview of the paragonimiasis research field, including current trends, development, and researcher collaboration. By addressing gaps in this bibliometric analysis and increasing collaboration, stake-holders could strengthen their strategies to effectively combat paragonimiasis and improve public health outcomes.
Keywords: Bibliometric; Paragonimiasis; Paragonimus westermanii